1996
DOI: 10.1002/(sici)1096-8652(199604)51:4<261::aid-ajh2>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

In vitro culture with prednisolone increases BCL-2 protein expression in adult acute lymphoblastic leukemia cells

Abstract: The presence of BCL-2 gene rearrangement has been detected also in cellular populations lacking the t(14;18) chromosomal translocation, such as B-lineage acute lymphoblastic leukemia (ALL) cells. It has been reported that overexpression of BCL-2 is related to resistance to glucocorticoid-induced apoptosis. In this study, we aimed to evaluate whether in vitro culture with prednisolone (PDN) could modify the expression of BCL-2 protein. ALL cells from 21 patients were incubated for 72 hr with or without a minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…This finding was unexpected since we had speculated that exposure of myeloma cells to anti-cancer agents might induce expression of Bcl-2. Indeed, expression of Bcl-2 was reported to be induced by exposure of leukemia cells to steroids, 13 and in vitro experiments showed that a high level of expression of Bcl-2 is known to mediate drug resistance. 2 Although analysis of more cases and further in vitro studies are necessary to clarify the phenomenon, the initial levels of expression of Bcl-2 and Bcl-X L may be more important than the induction of these proteins by chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was unexpected since we had speculated that exposure of myeloma cells to anti-cancer agents might induce expression of Bcl-2. Indeed, expression of Bcl-2 was reported to be induced by exposure of leukemia cells to steroids, 13 and in vitro experiments showed that a high level of expression of Bcl-2 is known to mediate drug resistance. 2 Although analysis of more cases and further in vitro studies are necessary to clarify the phenomenon, the initial levels of expression of Bcl-2 and Bcl-X L may be more important than the induction of these proteins by chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Also analysing Bcl-2 protein expression, Klampfer et al [36], demonstrated that treatment with sodium salicylate after 5 and 18 h did not alter the expression of the Bcl-2 proteins in the TF-1 acute myeloid leukaemia cell line. However, several authors reported that Bcl-2 protein expression in some tumoral cells is enhanced by chemotherapeutic drugs [41]. In relation to the biological model used in the present work, Zhang et al [34] observed that indomethacin (NSAID) down-regulates bcl-2 gene expression in K562 cells.…”
Section: Discussionmentioning
confidence: 66%
“…Bcl-2 up-regulation has not yet been reported to occur after in vivo administration of chemotherapeutic agents (Walton et al, 1993). Tosi et al (1996) have recently observed increased bcl-2 expression after prednisolone in vitro. In these studies, we show that high-dose HN2 up-regulates bcl-2 protein levels both in HT-29, a cell line that normally has low bcl-2 levels, and in MCF-7, a cell line normally expressing high levels of bcl-2.…”
Section: Discussionmentioning
confidence: 96%